2007
DOI: 10.1007/s00253-006-0648-3
|View full text |Cite
|
Sign up to set email alerts
|

Molecular cloning and heterologous expression of a new xylanase gene from Plectosphaerella cucumerina

Abstract: A gene encoding a new xylanase, named xynZG, was cloned by the genome-walking PCR method from the nematophagous fungus Plectosphaerella cucumerina. The genomic DNA sequence of xynZG contains a 780 bp open reading frame separated by two introns with the sizes of 50 and 46 bp. To our knowledge, this would be the first functional gene cloned from P. cucumerina. The 684 bp cDNA was cloned into vector pHBM905B and transformed into Pichia pastoris GS115 to select xylanase-secreting transformants on RBB-xylan contain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
42
2

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(47 citation statements)
references
References 26 publications
3
42
2
Order By: Relevance
“…Previous publications reported that EDTA was an inhibitor to some xylanases (Zhang et al 2007); however, in this study, EDTA at 0.25% did not affect enzyme activity (Table 2). This suggests that xylanases may have different catalytic mechanisms, and that Xyn10 is not a metalloenzyme.…”
Section: Discussioncontrasting
confidence: 79%
“…Previous publications reported that EDTA was an inhibitor to some xylanases (Zhang et al 2007); however, in this study, EDTA at 0.25% did not affect enzyme activity (Table 2). This suggests that xylanases may have different catalytic mechanisms, and that Xyn10 is not a metalloenzyme.…”
Section: Discussioncontrasting
confidence: 79%
“…As shown in Table 5 close vicinity with the active site of xylanase, and its interaction with sulfhydryl group led to strong inhibition of xylanase activity; similar observations were also reported for other xylanases (Beg et al 2001). The substantial effect of Hg 2+ (2.5%) on xylanase activity reveal the important participation of tryptophan residues in the catalytic action of enzyme; as Hg 2+ can oxidize the indole ring, it was believed to interact with aromatic ring present in tryptophan, contributing in decrease of xylanase activity Zhang et al 2007). The thiol group-bearing chemical agent β-mercaptoethanol (121.6%), the non-ionic detergent polysorbate 80 (115.2%), and the chelating agent EDTA (105.4%) all showed stimulatory effects on xylanase activity.…”
Section: Effect Of Metal Ions and Chemical Agentssupporting
confidence: 75%
“…Further, Hg 2? is known to oxidize indole ring and to interact with aromatic ring present in tryptophan (Zhang et al 2007;Liu et al 2010). NBS exerted very strong inhibitory action as in b-D-xylanase of B. halodurans, indicating the catalytic role of tryptophan (Kumar and Satyanarayana 2011).…”
Section: Discussionmentioning
confidence: 97%